The Influence of Profitability and Institutional Ownership on Firm Value: The Mediating Role of Dividend Policy - M Doni Permana Putra; Ketut Elly Sutrisni (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2026)
Purpose: This study investigates the determinants of firm value in the Indonesian property and real estate sector during the post-pandemic recovery period of 2022–2024. It specifically examines the effects of Profitability and Institutional Ownership on Firm Value, with Dividend Policy positioned as a mediating variable. Method: This study employs a quantitative approach using secondary data from property and real estate companies listed on the Indonesia Stock Exchange. The sample was selected through purposive sampling based on criteria such as continuous financial reporting, profitability, and dividend distribution, resulting in a balanced panel of eligible firms. The hypotheses were tested using path analysis. Findings: The results show that Profitability, proxied by ROA, has a significant positive effect on firm value but a significant negative effect on dividend policy, indicating that firms tend to prioritize internal financing over dividend distribution. Institutional Ownership has a significant positive effect on dividend policy but does not directly increase firm value. In addition, Dividend Policy does not mediate the relationship between Profitability and Firm Value, nor between Institutional Ownership and Firm Value. Implication: This study contributes to Signaling Theory and Agency Theory by showing that, in the Indonesian property sector, dividend payments may be interpreted as a reduction in growth capital rather than a positive market signal. Practically, the findings provide insights for investors and corporate managers in designing capital allocation and payout strategies during periods of sectoral recovery.